臺灣私設鐵道與日本各殖民地之比較：以私設鐵道補助為探討中心 - 張家端; 洪致文; Chia-Tuan Chang, Chih-wen Hung (地理學系, 2022)
日本在二戰前為了促進各地地方交通發展，於本土及殖民地（外地）均施行了私設／地方鐵道補助法，以推動與維持私設鐵道的發展與經營。以往雖多有針對臺灣私設鐵道的研究，但與日本各殖民地比較下，臺灣的特色究竟為何？這點則未被詳加討論。為此，本研究從地方交通為著眼點出發，研究日本各外地之私設鐵道地方交通網，以及為了促成或維持該交通網而訂定之私設鐵道補助法；以臺灣私設鐵道及補助法為中心，比較當時各殖民地，即朝鮮、樺太、南洋及滿洲（關東州與「滿洲國」）之私設鐵道，以及各自針對私設鐵道之補助概況。經過研究後發現，除了南洋不存在客運營業鐵道外，諸外地僅有臺灣大部分的地方交通在沒有私設鐵道補助的後盾下，自發形成綿密的路網，並可自給自足、維持經營，而這主要歸功於由製糖會社兼營之糖鐵營業線；至於朝鮮與樺太則透過補助以鼓勵並維持私設鐵道網的開展與經營；而滿洲則即便在補助的後盾下，私設鐵道仍然無法蓬勃發展。 Before World War II, in order to promote the development of local transportation, Japan implemented the Private/Local Railway Subsidy Act in the Japanese mainland and colonies to promote and maintain the development and operation of private railways. Although there have been many studies conducted on Taiwan's private railways in the past, this article examines the characteristics of Taiwan in comparison with other Japanese colonies. This topic has not yet been discussed in detail. Therefore, this article focuses on local transportation and studies the local transportation networks of private railways in Japanese colonies, as well as the private railway subsidy acts formulated to promote or maintain the transportation network. Focusing on Taiwan's private railways and subsidy act, this study compares Taiwan with the private railways of other Japanese colonies at that time, namely Korea, Karafuto (Sakhalin), South Seas Mandate and Manchuria, and their respective subsidies for private railways. This study finds that, apart from the absence of passenger railways in the South Seas, only the local transportation network in Taiwan was not backed by any private railway subsidies. A dense railway network was spontaneously formed and it was self-sufficient to maintain operations. This was mainly due to the networks of the sugar railway. As for Korea and Karafuto, subsidies were used to encourage and maintain the development and operation of private railway networks; whereas in Manchuria, even with the backing of subsidies, private railways still could not flourish.